Assessment the Relationship of Maternal Child Health Accessibility, Infant Mortality and Fertility in Sagar district, Madhya Pradesh - Kalyan Sundar Som (Indonesian Journal of Geography, 2019)
Equitable provision of health care services and full coverage of health accessibility are the major challenge for developing countries to achieve the sustainable development goal (SDG 3 and 10). A geographical information system (GIS) is an effective platform for knowing how much area and population are covered by the existing MCH (maternal child health) services network for better health care planning. The aim of this study is to assess the geographical accessibility of MCH services and how they give impact on infant mortality and fertility in Sagar District. To uncover the answer, this study used buffer zone analysis, service area analysis, and multiple regression analysis. The findings highlight lower accessibility has prevailed in the study area in which 41 percent village was underserved by the buffer zone analysis while 62 percent was underserved by the service area analysis out of 2075 village. It is diversified from higher accessibility in north western Khurai plain region to lower in the central upland exclude the Sagar community development Block. We also find that health accessibility can explain 53 percent of the infant mortality of the district and IMR may control 33 percent of the children ever born in the district.The service area and buffer mapped output may have policy implication for the future establishment of the health center and road network. This policy can be helpful for reducing infant mortality and fertility through this they achieved SDG target.